1996
DOI: 10.1046/j.1365-3059.1996.d01-96.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the amount of Verticillium dahliae in soil and the incidence of strawberry wilt as a basis for disease risk prediction

Abstract: The incidence of wilt was recorded in runner and fruiting crops of 13 strawberry cultivars at 72 locations in southern England in 1989 and 1990, and soil samples from the sites were analysed for Verticillium dahliae. Linear regressions of wilt incidence on inoculum concentration in soil for runner crops of the susceptible cv. Elsanta in both years were significant whilst that for runner crops of the susceptible cv. Hapil in 1989 approached significance; the regression for cv. Elsanta fruiting crops in 1990 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 14 publications
1
51
0
Order By: Relevance
“…In our study, the distribution of Verticillium wilt-diseased olive trees in the orchard followed aggregated patterns, similarly to that described for diseases caused by other soilborne pathogens (7). An aggregated pattern of diseased plants may correspond to an aggregated distribution of the pathogen in the primary source of inoculum, but also results from secondary infections by the spread of inoculum from primary foci to healthy plants (15) (4,18,34) at planting play a critical role in the spatial patterns of diseased plants and wilt development in many crops.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the distribution of Verticillium wilt-diseased olive trees in the orchard followed aggregated patterns, similarly to that described for diseases caused by other soilborne pathogens (7). An aggregated pattern of diseased plants may correspond to an aggregated distribution of the pathogen in the primary source of inoculum, but also results from secondary infections by the spread of inoculum from primary foci to healthy plants (15) (4,18,34) at planting play a critical role in the spatial patterns of diseased plants and wilt development in many crops.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential explanation is that even low densities of V. dahliae may incite high wilt incidences on strawberries. Harris and Yang (15) reported that on very susceptible cultivars, 3.8 CFU/g of soil incited 29% wilt. In our study, densities of V. dahliae in fumigated soils were lower than 2 CFU/g of soil, and wilt incidences in these soils were 15.3 and 24.4% in 2001 and 2002, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is a correlation between inoculum density and final disease incidence values (López Escudero and Blanco-López 2007; Bejarano- Alcázar et al 1995). Moreover, it has been observed that for a given inoculum density, disease incidence varies greatly depending on the crop (Berbegal et al 2007;Xiao and Subbarao 1998;Grogan et al 1979;Harris and Yang 1996;Atallah et al 2011). Consequently, validation and standardization of V. dahliae inoculation methods and inoculum density is needed to provide accurate assessment of wilt resistance in tree hosts.…”
Section: Management Of the Diseasementioning
confidence: 99%